Status of the Baltic/Wadden Sea population of the Common Eider Somateria m. mollissima. - Desholm, M; Christensen, T K; Scheiffarth, G; Hario, M; Andersson, Ã…; Ens, B; Camphuysen, C J; Nillson, L; Waltho, C M; Lorentsen, S-H; Kuresoo, A; Kats, R K H; et al. (Wildfowl, 2013)
x.